The use of colistin and other critical antimicrobials on pig and chicken farms in southern Vietnam and their association with resistance in commensal Escherichia coli - Nguyen, N; Nguyen, H; Nguyen, C; Nguyen, T; Nguyen, M; Thai, H; Ho, M; Thwaites, G; Ngo, H; Baker, S; Carrique-Mas, J (American Society for Microbiology, 2016)
Antimicrobial resistance (AMR) is a global health problem; emerging semi-intensive farming systems in Southeast Asia are major contributors to the AMR burden. We accessed 12 pig and chicken farms at key stages of production in the Tien Giang province (Vietnam) to measure antimicrobial usage and to investigate the prevalence of AMR against five critical antimicrobials (β-lactams, 3(th)cephalosporins, quinolones, aminoglycosides and polymyxins) and their corresponding molecular mechanisms among 180Escherichia coliisolates. Overall, 94.7mg (interquartile range (IQR) 65.3-151.1) and 563.6mg (IQR 398.9-943.6) of antimicrobials were used to produce 1kg of live weight of chicken and pig, respectively. A median of 3 (out of 8) critical antimicrobials was used on pig farms.E. coliisolates exhibited a high prevalence of resistance against ampicillin (97.8% and 94.4% for chickens and pigs, respectively), ciprofloxacin (73.3% and 21.1%), gentamicin (42.2% and 35.6%) and colistin (22.2% and 24.4%). The prevalence of recently discovered colistin resistance gene,mcr-1,was 19-22% and had strong agreement with phenotypic colistin resistance. We conducted plasmid conjugation experiments with 37mcr-1gene positiveE. coliisolates and successfully observed transfer of this gene in 54.0% isolates through a plasmid of approximately 63Kb, consistent with that identified earlier in China. We found no significant correlation between total usage of antimicrobials at farm level and AMR. These data provide additional insight into the role ofmcr-1in colistin resistance on farms in Asia and begin to outline the dynamics of phenotypic and genotypic AMR in semi-intensive farming systems in Vietnam.Our study provides accurate baseline information on levels of antimicrobial use, as well as on the dynamics of phenotypic and genotypic resistance for antimicrobials of critical importance amongE. coliover the different stages of production in emerging pig and poultry production systems in Vietnam.E. coliisolates showed a high prevalence of resistance (>20%) against critically important antimicrobials such as colistin, ciprofloxacin and gentamicin. The underlying genetic mechanisms identified for of colistin (mcr-1gene) and quinolone (gyrAgene mutations), are likely to play a major role in AMR to those compounds. Conjugation experiments led to the identification of a 63 Kb plasmid, similar to that recently identified in China, as the potential carrier of themcr-1gene. These results should encourage greater restrictions of such antimicrobials in southeast Asian farming systems.